Efficacy of artemether-lumefantrine and artesunate-amodiaquine for treating uncomplicated falciparum malaria in children - Tri Faranita; Ayodhia Pitaloka Pasaribu; Muhammad Ali; Munar Lubis; Syahril Pasaribu (Paediatrica Indonesiana, 2012)
Background Artesunate-amodiaquine (ASAQ) has been usedas a firsdine treatment for uncomplicated faldparum malariain Indonesia since 2004. Its efficacy depends on amodiaquineresistance of the infecting parasites. Artemether-lumefantrine(AL) has been shown to be highly efficacious in treatinguncomplicated faldparum malaria in several countries. However,there have been few studies on these anti-malarial medicationsin Indonesia.Objective To compare the efficacy of AL to ASAQ for treatinguncomplicated faldparum malaria in children.Methods An open, randomized, controlled trial wasconducted in school-aged children in the Mandailing NatalRegency, North Sumatera Province, Indonesia, from Octoberto December 2010. A total of 280 pediatric, uncomplicatedfalciparum malaria patients were randomly assigned to receiveeither AL or ASAQ for 3 days. Participants were followed-up ondays 1,2,3,7, 14, 28 and 42 following the first medication dose.The outcomes noted were adequate clinical and parasitologicalresponse (ACPR), parasite reduction, parasite clearance time,fever clearance time and adverse events. Analysis was basedon intention-to-treat.Results In this study, ACPRs on day 42 were 86.4% and 90.7%for the ASAQ and AL groups, respectively (p=0.260). On days 7and 14, the AL group had higher cure rates than that of the ASAQgroup (P<0.05). Early treatment failure, late treatment failure andparasitological failure for both groups were similar. We also foundfaster parasite clearance time and higher parasite reduction in theAL group than in the ASAQ group. However, fever clearancetime was shorter in the ASAQ group. The incidence of adverseevents such as nausea, vomiting, malaise, and pruritus were similarbetween the two groups (P=0.441).Conclusion AL had higher efficacy than ASAQ for the treatment of uncomplicated falciparum malaria in children.[Paediatr rndones. 2012;52:260-6].